2010
DOI: 10.1007/s10573-010-0020-x
|View full text |Cite
|
Sign up to set email alerts
|

Searching for ways to create energetic materials based on polynitrogen compounds (review)

Abstract: Polynitrogen compounds (containing only nitrogen atoms) are promising candidates as energetic materials for rocket engineering. The high energy content of these compounds is due to the significant difference in bond energy between nitrogen atoms. In particular, molecular nitrogen (N 2 ) is characterized by a uniquely strong triple bond -229 kcal/mole, whereas the single-bond energy is only 38.4 kcal/mole. From theoretical estimates, use of polynitrogen compounds can provide a specific impulse of 350-500 sec wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 75 publications
0
64
0
Order By: Relevance
“…For conventional CAHANAO-based propellants or explosives, increasing the energy content becomes very difficult because their energy thresholds are approaching their limits of stability. Professor Dong [1] confirmed that the increase is not more than 30% in performance for CAHANAO-based explosives, and the upper limit of density is approximately 2.3 g/cm 3 .…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…For conventional CAHANAO-based propellants or explosives, increasing the energy content becomes very difficult because their energy thresholds are approaching their limits of stability. Professor Dong [1] confirmed that the increase is not more than 30% in performance for CAHANAO-based explosives, and the upper limit of density is approximately 2.3 g/cm 3 .…”
Section: Introductionmentioning
confidence: 93%
“…As a result, some polynitrogen molecules were theoretically investigated in this article. A major motivation for this research is that polynitrogen molecules are expected to release a large amount of energy when they decompose into N 2 molecules . Therefore, these species are potentially promising as high‐energy‐density materials (HEDMs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cyc-N 3 isomer, on the other hand, lies about 30 kcal mol −1 above this spin-forbidden limit and shows a large barrier to isomerization or dissociation, 34 which makes it a good candidate as a high energy density material. 12,13 For this reason, it has received considerable attention, and has been already detected experimentally, [6][7][8][9] but not isolated yet.…”
Section: The 4 a And 2 A Statesmentioning
confidence: 99%
“…Although the linear one is widely known experimentally, 1-5 the ring form has only recently 6-11 been detected but its isolation remains elusive. As a nitrogen allotrope, it has potential applications as a high-energy density material, 12,13 and its natural tendency to dissociate to molecular nitrogen would make it a "clean" propellant.…”
Section: Introductionmentioning
confidence: 99%